2021
DOI: 10.1007/s10157-021-02021-y
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Alox15 improves kidney dysfunction and inhibits fibrosis by increased PGD2 in the kidney

Abstract: Background Lipid-metabolizing enzymes and their metabolites affect inflammation and fibrosis, but their roles in chronic kidney disease (CKD) have not been completely understood. Methods To clarify their role in CKD, we measured the mRNA levels of major lipid-metabolizing enzymes in 5/6 nephrectomized (Nx) kidneys of C57BL/6 J mice. Mediator lipidomics was performed to reveal lipid profiles of CKD kidneys. Results I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Macrophage infiltration and renal fibrosis were demonstrated to decrease in both ALOX15-knockout and inhibitor-treated mice but were increased in transgenic ALOX15overexpressing mice [41], and although that study did not include an in vitro analysis and the results from human macrophages, these results are consistent with our results obtained here. Additionally, studies of mice undergoing remnant nephrectomy, diabetic nephropathy, and sepsis-induced acute kidney injury had a similar profibrotic role of ALOX15 [52][53][54]. Consistent with these studies, the ALOX15 expression levels were found to be significantly higher in the kidneys of patients with advanced diabetic nephropathy, one of the main complications of diabetes [55].…”
Section: Discussionsupporting
confidence: 64%
“…Macrophage infiltration and renal fibrosis were demonstrated to decrease in both ALOX15-knockout and inhibitor-treated mice but were increased in transgenic ALOX15overexpressing mice [41], and although that study did not include an in vitro analysis and the results from human macrophages, these results are consistent with our results obtained here. Additionally, studies of mice undergoing remnant nephrectomy, diabetic nephropathy, and sepsis-induced acute kidney injury had a similar profibrotic role of ALOX15 [52][53][54]. Consistent with these studies, the ALOX15 expression levels were found to be significantly higher in the kidneys of patients with advanced diabetic nephropathy, one of the main complications of diabetes [55].…”
Section: Discussionsupporting
confidence: 64%
“…By analyzing the overlap between upregulated genes in nonstripped aortas from Ang II-treated TKO versus Cre mice with the downregulated transcripts in the anti-IL-9 mAb-treated TKO aortas, we identified potential genes involved with reversal of perivascular fibrosis, including Alox15 and Hp (Figure S12J). [47][48][49] We also compared the significant downregulated transcripts from the nonstripped aortic anti-IL-9 mAb treatment with the significant upregulated transcripts from aortic fibroblasts of Ang II treated TKO versus Cre mice to identity transcripts uniquely changed in fibroblasts after anti-IL-9 mAb rescue (Figure 8G). Indeed, the profibrotic genes Col8a1, Mmp2, Fmod, and Angptl1, which were identified as significantly increased in TKO aortas and in isolated fibroblasts by both bulk RNA seq and scRNA seq (Figure 7M), were all decreased after treatment with anti-IL-9 mAbs (Figure 8G).…”
Section: Neutralization Of Endogenous Il-9 Reversed the Ang Ii-induce...mentioning
confidence: 99%
“…Macrophage in ltration and renal brosis were demonstrated to decrease in both ALOX15-knockout and inhibitor-treated mice but were increased in transgenic ALOX15overexpressing mice [42], and although that study did not include an in vitro analysis and the results from human macrophages, these results are consistent with our results obtained here. Additionally, studies of mice undergoing remnant nephrectomy, diabetic nephropathy, and sepsis-induced acute kidney injury had a similar pro brotic role of ALOX15 [50][51][52] . Consistent with these studies, the ALOX15 expression levels were found to be signi cantly higher in the kidneys of patients with advanced diabetic nephropathy, one of the main complications of diabetes 53 .…”
Section: Discussionmentioning
confidence: 93%